Transcription factor Krüppel-like factor 5-regulated N-myc downstream-regulated gene 2 reduces IL-1β-induced chondrocyte inflammatory injury and extracellular matrix degradation. Issue 1 (1st January 2021) - Mei, Xiaoliang; Din, Hao; Zhao, Jianning; Tong, Jian; Zhu, Wei
ABSTRACT: Previous research has identified N-myc downstream-regulated gene 2 (NDRG2) as one of the differentially expressed genes common to rat models of osteoarthritis (OA) and human OA. The purpose of this study was to investigate the role of NDRG2 in OA. In this study, an in vitro OA model was constructed by challenging ATDC5 chondrocytes with 10 ng/ml IL-1β. After transfection of pcDNA3.1(+)/NDRG2, qPCR and western blot were performed to assay NDRG2 expression. The analyses of cell viability, apoptosis and inflammatory molecule expression were employed respectively by CCK-8, TUNEL and ELISA. The protein expression related to apoptosis, inflammation or extracellular matrix (ECM) degradation was detected by western blot. The binding of Krüppel-like factor 5 (KLF5) to NDRG2 promoter was verified by means of dual-luciferase reporter assay. After overexpression of both NDRG2 and KLF5 in IL-1β-stimulated ATDC5 chondrocytes, corresponding assays were performed to examine cell viability, apoptosis, inflammatory response and ECM degradation. In ATDC5 chondrocytes challenged with IL-1β, NDRG2 expression was much lower than that in the control group, whereas it's overexpression helped restored cell viability and reduce cell apoptosis, inflammatory response and ECM degradation. It was also observed that KLF5 expression was decreased in IL-1β-stimulated ATDC5 chondrocytes, and that KLF5 bound to the NDRG2 promoter. Importantly, overexpressing KLF5 could reverse the protective effect of NDRG2 overexpression on IL-1β-stimulated ATDC5. Overall, NDRG2 could be transcriptionally regulated by transcription factor KLF5 and may play a protective role against chondrocyte the inflammatory response and ECM degradation in OA.